2020
DOI: 10.1177/0192623320964748
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as an Animal Model for Ocular Toxicity Testing: A Review of Ocular Anatomy and Functional Assays

Abstract: Xenobiotics make their way into organisms from diverse sources including diet, medication, and pollution. Our understanding of ocular toxicities from xenobiotics in humans, livestock, and wildlife is growing thanks to laboratory animal models. Anatomy and physiology are conserved among vertebrate eyes, and studies with common mammalian preclinical species (rodent, dog) can predict human ocular toxicity. However, since the eye is susceptible to toxicities that may not involve a histological correlate, and these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 197 publications
(296 reference statements)
0
11
0
Order By: Relevance
“…Some of materials may produce adverse effects on reproduction (teratogenicity) and may lead to DNA damage and therefore, Caenorhabditis elegans is a suitable model for screening cytotoxicity studies [60]. Additionally, Zebrafish and its embryo has been extensively used for studying effects of materials to the ocular, cardiovascular and neural differentiation [61][62][63][64]. Some of the in vitro models used in cytotoxicity studies of biomaterials are shown in table 1.…”
Section: Assays For Biomaterials Cytotoxicity Assessmentmentioning
confidence: 99%
“…Some of materials may produce adverse effects on reproduction (teratogenicity) and may lead to DNA damage and therefore, Caenorhabditis elegans is a suitable model for screening cytotoxicity studies [60]. Additionally, Zebrafish and its embryo has been extensively used for studying effects of materials to the ocular, cardiovascular and neural differentiation [61][62][63][64]. Some of the in vitro models used in cytotoxicity studies of biomaterials are shown in table 1.…”
Section: Assays For Biomaterials Cytotoxicity Assessmentmentioning
confidence: 99%
“…Zebrafish embryos develop most of the major organ systems present in mammals, including the cardiovascular, nervous and digestive systems, in in less than a week and most of the safety and efficacy assays can be carried out with zebrafish embryo and larvae with data generated biologically relevant [4]. To endorse the 3Rs principles, the tests chosen for the toxicological screening used zebrafish embryos and larvae up to 120 hpf, classified as in vitro models by international Directives.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish embryos and larvae with up to 120 h of life have been considered unprecedented toxicological models, which exhibit a diverse repertoire of biological processes and possess fully integrated vertebrate organ systems [3]. Thus, zebrafish can bridge the gap between in vitro safety assays and mammals' models in a fast and cost-effective manner and would have a key role in accelerating the process of new chemicals development, improving prediction, prioritizing safe compounds, and decreasing testing time and costs substantially [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important advantages are the small size (reduction in maintenance costs and spaces to be used), high fecundity, and rapidity of embryonic development [31]. This fascinating model can be utilized in mutagenesis analyses and drug screening tests [32][33][34]. It has become a popular model organism used to conduct experiments related to different research fields, such as embryology, genetics, cancer, cardiovascular, and organ and tissue regeneration [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%